Expanding Horizons in Complement Analysis and Quality Control - Frazer-Abel, Ashley; Kirschfink, Michael; Prohászka, Zoltán (Frontiers in Immunology, 2021)
Complement not only plays a key role in host microbial defense but also modulates the adaptive immune response through modification of T- and B-cell reactivity. Moreover, a normally functioning complement system participates in hematopoiesis, reproduction, lipid metabolism and tissue regeneration. Due to its powerful inflammatory potential multiple regulatory proteins are needed to prevent potential tissue damage. In clinical practice, dysregulation and overactivation of the complement system are major causes of a variety of inflammatory and autoimmune diseases ranging from nephropathies, age-related macular degeneration (AMD), and systemic lupus erythematosus (SLE) to graft rejection, sepsis and multi-organ failure. The clinical importance is reflected by the recent development of multiple drugs targeting complement with a broad spectrum of indications. The recognition of the role of complement in diverse diseases and the advent of complement therapeutics has increased the number of laboratories and suppliers entering the field.Thishas highlighted the need for reliable complement testing.The relatively rapid expansion in complement testing has presented challenges for a previously niche field.This is exemplified by the issue of cross-reactivity of complement-directed antibodies and bythe challenges of the poor stability of many of the complement analytes. The complex nature of complement testing and increasing clinical demand has been met in the last decade by efforts to improve the standardization among laboratories. Initiated by the IUIS/ICS Committee for the Standardization and Quality Assessment in Complement Measurements 14 rounds of external quality assessment since 2010 resulted in improvements in the consistency of testing across participating institutions, while extending the global reach of the efforts to more than 200 laboratories in 30 countries. World-wide trends of assay availability, usage and analytical performance are summarized based on the past years’ experiences. Progress in complement analysis has been facilitated by the quality assessment and standardization efforts that now allowcomplement testing to provide a comprehensive insight into deficiencies and the activation state of the system. This in turn enables clinicians to better define disease severity, evolution and response to therapy.